10 years follow‐up after mid‐urethral sling implantation: high rate of cure yet a re‐occurrence of OAB‐symptoms. Issue 3 (9th February 2016) - Schauer, Ingrid; Bock, Helena; Eredics, Klaus; Wallis, Martina; Scholz, Michael; Madersbacher, Stephan; Lüftenegger, Werner
Abstract : Aims: To assess the long‐term outcome of mid‐urethral slings regarding urinary incontinence (UI) and lower urinary tract symptoms and to identify risk factors for an unsatisfactory outcome. Methods: Analysis of a prospective institutional database. For the current analysis only women who reached the 10 years follow‐up were eligible. Outcome was assessed using a detailed, non‐validated questionnaire on continence status and on several aspects of lower urinary tract function. Results: A total of 256 women were operated during 1999–2004, in 139 (54.3%), a 10 years follow‐up was available and these patients were included. Mean age at surgery was 63 years. At the 2, 5, and 10 years follow‐up, the percentages of women reporting 0–1 pads/day were 96.4%, 97.1% and 88.5%, respectively. More than 95% of the patients reported no stress UI at the 2, 5, and 10 years follow‐up. At baseline, urgency was reported by 61.2%, this figure dropped to 17.3% at 2 years and increased thereafter to 32.4% (5 years) and 41.7% (10 years). De novo urgency was present in 3.6% after 2 years, in 10.8% after 5 years, and 14.4% after 10 years. The percentage of patients with a high degree of treatment satisfaction declined from 79.1% at 2 years to 70.5% at 5 years, and 62.6% at 10 years. Risk factors for an unsatisfactory long‐term outcome were advanced age, the presence of urgency, nocturia, and decreased bladder capacity at baseline. Conclusions: This study confirms the excellent long‐term efficacy of mid‐urethral slings regarding the management of stress UI. A substantial number of women develop OAB‐symptoms after the procedure that largely contribute to outcome dissatisfaction. Neurourol. Urodynam. 36:614–619, 2017 . © 2016 Wiley Periodicals, Inc.